2021
DOI: 10.3390/math9202622
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Studies of Financial Bankruptcy Prediction Using Advanced Hybrid Intelligent Classification Models to Provide Early Warning in the Electronics Industry

Abstract: In recent years in Taiwan, scholars who study financial bankruptcy have mostly focused on individual listed and over-the-counter (OTC) industries or the entire industry, while few have studied the independent electronics industry. Thus, this study investigated the application of an advanced hybrid Z-score bankruptcy prediction model in selecting financial ratios of listed companies in eight related electronics industries (semiconductor, computer, and peripherals, photoelectric, communication network, electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
(62 reference statements)
0
13
1
Order By: Relevance
“…Financial liquidity in this context is defined as an ability to convert assets into cash in the shortest possible time and without losing their value, with the lowest transaction costs associated with this exchange. Financial liquidity is identified as being the most important determinants affecting the predictor of financial bankruptcy (Chen et al 2021;Chłodnicka and Zimon 2020). Financial liquidity and profitability are strongly related to working capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financial liquidity in this context is defined as an ability to convert assets into cash in the shortest possible time and without losing their value, with the lowest transaction costs associated with this exchange. Financial liquidity is identified as being the most important determinants affecting the predictor of financial bankruptcy (Chen et al 2021;Chłodnicka and Zimon 2020). Financial liquidity and profitability are strongly related to working capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, variables that utilize firm characteristics are listed, and the foundation years, firm size (market value), debt rates, EPS, and enterprises’ new investment activity intent (Tobin’s Q ; Liu, 2021) are analyzed. Chen et al (2021) used financial ratios to study capital gains and losses in stock markets. Excluding the unpredictable limitation view of the stock market, data mining and artificial intelligence methods were used to study stock market capital gains and losses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The established tree structure model summarizes important rules and makes predictions for unknown samples. It is widely used in finance (Basak et al, 2019; Chen et al, 2021; Coelho et al, 2007). For example, bankruptcy prediction models have been used to build financial crises in Taiwan’s electronics industry (Chen et al, 2021) and apply detection models for stock market manipulation (Liu et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Jabeur (2017) developed a logistic model for French companies using 33 financial ratios. Chen et al (2021) predicted bankruptcy in Taiwan's electronics industry based on data from 2000 to 2019. Out of the 22 financial indicators used, the authors found that three affect corporate bankruptcy the most: liquidity ratio, debt ratio, and fixed assets turnover ratio.…”
Section: Literature Reviewmentioning
confidence: 99%